2009
DOI: 10.3155/1047-3289.59.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Performance of an Activated Carbon Biofilter Degrading Styrene: Effects of Residence Time and Inlet Concentration

Abstract: A granular-activated-carbon-packed biofilter receiving a constant loading rate of styrene was subjected to changes in residence time and concentration, and the effects on performance characteristics and the composition of biofilm along the bed height in the biofilter were studied. This study was carried out during the last 3 months of the entire biofilter operation of 16 months. The total bed height of the biofilter was physically divided into four individual reactor stages in series. This configuration permit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
1
5
1
Order By: Relevance
“…This phenomenon was observed despite the fact that the first stage accounted for the majority of the biofilter elimination capacity and was particularly pronounced with gasoline as a substrate (Figures 6a and 6b). This pattern seems to contradict our earlier observations obtained with other hydrocarbon mixtures (Paca et al, 2009a;Paca et al, 2009b), as well as the common paradigm that the pH drop increases along with the biodegradation rate, that is, is greater in the first stage. Also, CO 2 releasing during biodegradation can cause some drop of pH.…”
Section: Rate-limiting Step Determination: Removal Of Individual N-alcontrasting
confidence: 99%
See 2 more Smart Citations
“…This phenomenon was observed despite the fact that the first stage accounted for the majority of the biofilter elimination capacity and was particularly pronounced with gasoline as a substrate (Figures 6a and 6b). This pattern seems to contradict our earlier observations obtained with other hydrocarbon mixtures (Paca et al, 2009a;Paca et al, 2009b), as well as the common paradigm that the pH drop increases along with the biodegradation rate, that is, is greater in the first stage. Also, CO 2 releasing during biodegradation can cause some drop of pH.…”
Section: Rate-limiting Step Determination: Removal Of Individual N-alcontrasting
confidence: 99%
“…As we observed previously, Pseudomonas bacteria are widespread in biofilm reactors for wastewater treatment and are able to degrade a wide range of aromatic and aliphatic hydrocarbons (Paca et al, 2007;Paca et al, 2009a;Paca et al, 2009b;Paca et al, 2010). Other authors also reported a versatile and diverse hydrocarbon degrading activity of Pseudomonas bacteria (Song et al, 2006;Duarte da Cunha and Leite, 2000;Das and Chandran, 2011).…”
Section: Influence Of the Pollutant Switch On The Biofilm Compositionsupporting
confidence: 67%
See 1 more Smart Citation
“…Other designs were also proposed, e.g., a pilot multistage tower fermenter [74,84]. A design for venting bioWlters has also been proposed [76,77].…”
Section: Bioreactor Design and Control Strategiesmentioning
confidence: 99%
“…Strains of these genera are frequently described as efficient VOC degraders. [3,11,28,29] All recovered fungal species, Aspergillus sp., Cephalosporium sp., Cladosporium sp., Penicillium sp., were also primary degraders of both substrates as consistent with literature where they are described as versatile degraders of a wide range of VOCs. [3,28,30,31] Flies as a means of the biomass control in the BF In addition to microorganisms, flies were found in the biofilter (Fig.…”
Section: Microbial Analysismentioning
confidence: 99%